A gestão ambiental de Belo Horizonte através da arborização urbana: da estruturação urbana rumo à infraestrutura sustentável - Júlio César De Marco (2020)
The adoption of sustainable infrastructure networks is a challenged posed to local governments which have incorporated the Sustainable Development Objectives -SDO- in their territorial management agendas once they haven´t yet been properly characterized. With a view to consider urban arborization an element of such a network, the case study of Belo Horizonte´s municipality is taken, where it assumes a prominent role in the politics in environmental management as concerning the aesthetic composition of urbanscape, which implied the creation of a Three Inventory and Information System – SIIA-BH – with emphasis on tree management. Quantifying and valuating the services rendered by urban trees along streets and public spaces regarding the achievement of local goals related to mitigating the effects of climate changes and the territorial vulnerabilities due to these effects is proposed as a means to amplifying its utilization, also, as an instrument for urban-environmental planning and patrimonial management. Hence, it´s necessary to understand this arborization and the spaces it characterizes, both bearing in mind the historic processes of its creation, since the planning of the city based on utopic urban models from the 19th. century, and its evolution, and, also, the processes performed by trees related to typical services rendered by a sustainable infrastructure. Methodologically, via historic and comparative approaches, it was built an unprecedented knowledge repository about Belo Horizonte´s urban arborization, and via inductive proceedings, considering the state of the art of sustainable infrastructure and transversal and complementary concepts such as green infrastructure, ecosystem services, ecosystem regeneration and nature based solutions –NbS-, it´s proposed a systematization complying with the interaction and the hierarchy of those concepts so to characterize the sustainable infrastructure as well a procedure for the creation of classes of services in the system SIIA-BH, based on such a systematization and on the goals concerning with local environmental managing, bearing in mind international collaboratives platforms.